Homozygous missense MYBPC3 Pro873His mutation associated with increased risk for heart failure development in hypertrophic cardiomyopathy. (16th April 2018) - Kissopoulou, Antheia; Trinks, Cecilia; Green, Anna; Karlsson, Jan‐Erik; Jonasson, Jon; Gunnarsson, Cecilia
Abstract: Hypertrophic cardiomyopathy (HCM) is a primary autosomal‐dominant disorder of the myocardium with variable expressivity and penetrance. Occasionally, homozygous sarcomere genetic variants emerge while genotyping HCM patients. In these cases, a more severe HCM phenotype is generally seen. Here, we report a case of HCM that was diagnosed clinically at 39 years of age. Initial symptoms were shortness of breath during exertion. Successively, he developed a wide array of severe clinical manifestations, which progressed to an ominous end‐stage heart failure that resulted in heart transplantation. Genotype analysis revealed a missense MYBPC3 variant NM_000256.3:c.2618C>A, p.(Pro873His) that presented in the homozygous form. Conflicting interpretations of pathogenicity have been reported for the Pro873His MYBPC3 variant described here. Our patient, presenting with two copies of the variant and devoid of a normal allele, progressed to end‐stage heart failure, which supports the notion of a deleterious effect of this variant in the homozygous form.